Bioconversion by gut microbiota of predigested mango (Mangifera indica L) 'Ataulfo' peel polyphenols assessed in a dynamic (TIM-2) in vitro model of the human colon. (January 2021) - Sáyago-Ayerdi, Sonia G.; Venema, Koen; Tabernero, Maria; Sarriá, Beatriz; Bravo, L. Laura; Mateos, Raquel
Graphical abstract: Highlights: Bioconversion of mango peel (MP) phenols by gut microbiota was assessed using TIM-2. Derivatives of phenylpropionic, phenylacetic and benzoic acids were mainly identified. Microbial metabolites derived from flavonoids, gallates and gallotannins in MP. Ellagic acid present in MP was mainly transformed into urolythins A and C. Xanthone and benzophenone derivatives remained after the colonic bioconversion. Abstract: Gut microbiota bioconversion of polyphenols in predigested mango 'Ataulfo' peel was studied using a validated, dynamic in vitro human colon model (TIM-2) with faecal microbial inoculum. Dried peels were predigested with enzymatic treatment, followed by TIM-2 fermentation (72 h). Samples were taken at 0, 24, 48 and 72 h and analyzed by HPLC-QToF. Derivatives of hydroxyphenylpropionic, hydroxyphenylacetic and hydroxybenzoic acids, as well as, pyrogallol were the main polyphenols identified. These metabolites might derivate from flavonoid (flavanols and flavonols), gallate and gallotannin biotransformation. Despite the high content of ellagic acid in mango peel, low amounts were detected in TIM-2 samples due to transformation into urolythins A and C, mainly. Xanthone and benzophenone derivatives, specific to mango, remained after the colonic biotransformation, contrary to flavonoids, which completely disappeared. In conclusion, microbial-derived metabolites, such as xanthone and benzophenone derivatives, among others, are partially stable after colonic fermentation, and thus have the potential to contribute to mango peel bioactivity.